Magnetic damping and perpendicular magnetic anisotropy in Pd-buffered [Co/Ni]5 and [Ni/Co]5 multilayers. Issue 9 (17th January 2017) - Tang, Minghong; Li, Wei; Ren, Yang; Zhang, Zongzhi; Lou, Shitao; Jin, Q. Y.
Abstract : The magnetic damping α 0 increases continuously with underlayer thickness, showing no correlation with PMA strength but a similar variation behavior to 1/ M s . Such α 0 increase is ascribed to the formation of more disordered spins at NM/FM interface. Abstract : We systematically studied the influence of Pd underlayer on the magnetic properties of perpendicular [Co/Ni]5 and [Ni/Co]5 multilayers by time-resolved magneto-optical Kerr effect. We found that the saturated magnetic damping constant α 0 increases continuously with increasing the Pd thickness t Pd, showing no linear correlation with the perpendicular magnetic anisotropy constant K u for both series of samples. As compared to the Co/Ni sample with the same t Pd, the Ni/Co film shows lower saturation magnetization, weaker K u but larger α 0, which can be ascribed to the presence of more paramagnetic spins at the Pd/Ni interface due to the weak exchange coupling stiffness between Ni atoms. By analyzing extrinsic damping contributions from magnetic inhomogeneities, two-magnon scattering and spin pumping effects, the intrinsic damping of perpendicular [Ni/Co]5 is quantitatively determined to be 0.023. This study should provide deep understanding and effective control of magnetic damping for designing high performance magnetic memory devices.